PRODUCTION OF BIODIESEL FROM JATROPHA FRUIT (Jatropha Curcas) - Ridwan, R (Politeknik Negeri Lhokseumawe, 2024)
ABSTRACT The energy crisis has led to rising petroleum prices. To address this issue, alternative fuels need to be sought. This study aims to utilize oil from the Jatropha plant (*Jatropha curcas*) to produce biodiesel through a transesterification reaction. The research was conducted using Jatropha oil-to-methanol ratios of 1:3, 1:4, and 1:5, with transesterification reaction times of 2 hours, 2.5 hours, and 3 hours. The results showed that the optimum volume of methyl ester from the transesterification reaction was achieved with a 1:4 ratio and a reaction time of about 2 hours.Keywords: Biodiesel, Jatropha plant, transesterification reaction